Prevalência de percepção de idosos sobre seu risco de quedas e fatores associados - Agulhó, Daniela Luzia Zagoto (2017)
ABSTRACT: Among the causes of death that have affected the elderly population, accidents due to falls are an important problem, and consequently, represent a public health problem. Several factors can influence the occurrence of falls, among them the perception of risk. Every elderly person, endowed with his own beliefs and conceptions, has a different view of the falls. This, in turn, reflects in the perception that each one has about his risk of falling, consequently in the behavior of prevention of falls. Objective: To analyze the prevalence of the perception of the elderly about their risk of falls, their reasons and the factors associated with this perception. Method: Cross-sectional and analytical study performed with elderly participants of the Healthy Longevity Program of UFMT. The sample of the study was nonprobabilistic of convenience type, composed of 190 elderly. Data collection was performed through an interview using a sociodemographic questionnaire on health conditions and risk perception, Falls Risk Score, Falls Efficacy Scale, Katz Index and Lawton & Brody Scale. The technique of vignette was also used to evaluate the perception that the elderly had about their risk of falls, an instrument elaborated with 12 images of situations and risk environments, submitted to content validation. Descriptive analysis with absolute and relative frequency and bivariate statistical analysis were performed to verify the possible associations through the chisquare test (x2). It was also applied to multiple logistic regression to identify the factors associated with the perception of the elderly about their risk of falls. The stepwise forward method was used to select the variables for assembly of the model considering p <0.20 in the bivariate analysis. Results: 63.7% of the elderly do not perceive themselves at risk of falling. The elderly's reasons for not being at risk of falling are related to the aging process, their behaviors and conceptions regarding the risks of falls. The factors associated with the low perception of the elderly on their risk of falls were mobility (p = 0.018) and concern that the elderly had to fall (p = 0.002). Conclusion: These results are of concern in that these elderly people, when they do not perceive themselves at risk, can adopt risk behaviors that, as a consequence, result in falls and their consequences. These findings indicate the need for greater investments in programs / groups that include activities that increase the perception of the elderly to the risks of falls, using strategies that allow them to recognize themselves as potential hunters and need to adopt preventive measures in their day to day.